The Impacts of Oath of Knowledge Denial in Jurisprudence and Iranâs Law - Ã™Â…Ã˜Â§Ã™ÂÃ›ÂŒ, Ã˜Â¯ÃšÂ©Ã˜ÂªÃ˜Â± Ã™Â‡Ã™Â…Ã˜Â§Ã›ÂŒÃ™ÂˆÃ™Â†; Ã˜Â±Ã˜Â¶Ã˜Â§Ã›ÂŒÃ›ÂŒ Ã™Â…Ã™Â‚Ã˜Â¯Ã™Â…, Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The proofs presented to the court of justice for proving or defending a legal case, if proved effective, have certain impacts that the necessity of knowing them in order to timely use the âproofâ in legal procedure and success in it cannot be ignored. Among these proofs is the oath of knowledge denial, which due to the silence of the legislator and the juristsâ diversity of views, studying its outcomes requires further in-depth consideration to achieve the above-mentioned propositions. The oath of knowledge denial is in fact a decisive (battÄ«) oath that can comprise of specific effects on the claim of knowledge and the main claim. Similarly, in case of refusal, it can have considerable effect on the claim in terms of rejecting the oath and swearing rejected oath by the claimant. Also, by accepting the existence of some similar effects between the oath of knowledge denial and other types of oath, the exemption from swearing a decisive oath and the non-provability of the main claim by swearing is considered to be among the specific effects of the oath of knowledge denial.